Suspended sediment concentration distribution in an alluvial channel flow - Chung, Dang Huu (Vietnam Journal of Mechanics, 1994)
In this paper a numerical solution for the problem on suspended sediment concentration distribution in an alluvial channel flow has been computed on the base of PROFILE model proposed by L. C. Van Rijn for the case of uniform flow. Although, in the present case, mathematical model is quite simple, but it is exact enough to apply to Somme problems in practice. The aim of the paper is that the author would like to use the finite difference method for the same problem. The input data was used from experiment flume. The result showed that the concentration distribution fast decreased along the channel and concentration gradients became very small at the sections situated far enough from the upstream. Besides, a computing program me with the ability of graphic expression was established.